Complete conditioning for basketball - Foran, Bill;Pound, Robin (Illinois : Human Kinetcs, 2007)
A guide to performance factors, training direction and workouts. This book includes a DVD that offers on-court demonstration of drills, which guide basketball coaches and players to make the best possible decisions about their conditioning.
Tests and evaluation -- Warm-up and flexibility -- Conditioning -- Strength -- Power -- Speed -- Agility -- Complete conditioning schedule
Includes index.
Keywords: BASKETBALL -- TRAINING